PENGARUH KOMPONEN STRUKTUR PENGENDALIAN INTERNAL UNTUK MENCEGAH KECURANGAN PADA PERUSAHAAN - SOFIANINGSIH, DEWI (Jurnal Akuntansi AKUNESA, 2014)
The purpose of this study is to analyze an find out the influence of the control structurescomponents internal to prevent cheating on the company. To prevent on corporations,starting from an internal control. To treat or prevent fraud on government agency, thepreventive effort is required with regard to how to control the driving factor for incidence offraud. To implement the strategy, the internal control system should be applied effectively.The effectiveness of legal provisions could not be achieved if not supported norms and ethicalvalues from related parties. In addition to internal controls there are two other key conceptsin the prevention of fraud, fraud awareness and fraud risk assessment. The results of thisresearch are important for internal controls to prevent fraud on the company. In theprevention if an internal control structures have been placed and run well, opportunities forfraud that are not detected will be reduced.Keywords : fraud, internal control, fraud awareness, fraud risk assessment.